The negative effects of waste on the urban environment in the city of Khums (Waste to sustainable energy) - Waled Abdulslam Freewan; Abdalsalam Mohamed Alrachidy (Journal of Pure & Applied Sciences, 2022)
Waste is one of the biggest problems faced by some countries of the world, especially in developing countries, and this matter is due to several reasons, including the increasing population density, the lack of awareness among most segments of society, the adoption of incorrect methods to get rid of it, as well as the spread of bad smell and annoying scenes, and for this Solutions had to be found, either through reuse and recycling, or by converting them into energy sources. One of the common problems at the present time is the frequent blackouts in many cities in Libya for long periods, to solve this problem must be found a possibility of providing clean, renewable energy, and as the idea of converting waste into energy sources is not modern, and it is currently considered the third source of energy Renewable. That is why this study was concerned with spreading the culture of using sustainable renewable energies and the role of the faculty member in supporting them. For this, a questionnaire was made and distributed electronically to a segment of faculty members in the Department of Architecture in higher education institutions in Libya.